Spatial and vertical extent of nucleation events in the Midwestern USA: insights from the Nucleation In ForesTs (NIFTy) experiment - S. C. Pryor; R. J. Barthelmie; L. L. Sørensen; J. G. McGrath; P. Hopke; T. Petäjä (Atmospheric Chemistry and Physics, 2011)
Measurements of aerosol particle physical and chemical properties, gas phase concentrations and meteorological parameters were made along a transect in southern Indiana during the Nucleation In ForesTs (NIFTy) experiment conducted in May 2008. These measurements indicate nucleation was observed at all three measurement sites on almost half of all sampling days. The intensity of the nucleation events, as measured by the increase in ≥10 nm aerosol particle number concentrations of approximately 2×104 cm−3 over a layer of at least 300 m depth, is in good agreement with recent model results for the Midwestern USA derived using PMCAMx-UF. During the hour after termination of nucleation approximately half of the number concentration reduction is due to coagulation, while the remainder is due in equal parts to dry deposition and entrainment of relatively ultra-fine aerosol particle free troposphere air. Clear nucleation with continuous subsequent growth is only observed on days when the morning fractional cloud cover was less than 30%. It is associated with a clear transition from a strongly stratified atmosphere with low turbulence intensity and weak vertical velocities, to much a weaker vertical gradient of wind speed, increased turbulence intensity and stronger downwards vertical velocities, consistent with growth of the mixed layer and entrainment of air from the residual layer. Nucleation intensity is not very strongly determined by the prevailing condensational sink. However, there is a strong correlation between both a modified version of the Nucleation Parameter from Boy and Kulmala (2002) and ultrafine aerosol particle number concentrations, and mean morning H2SO4 concentrations and ultrafine aerosol particle number concentrations. Five A-class event days during NIFTy were characterized by values of the dimensionless nucleation parameter of Kuang et al. (2010) that are below 0.3, further indicating the applicability of their postulate that nucleation is favored by LΓ values below 0.7. Based on aerosol particle composition measurements it appears that aerosol particle formation and initial growth to approximately 30 nm diameter is dominated by ammonium and sulfate. Conservative estimates of the percent contribution of H2SO4 to aerosol particle growth (for sub-30 nm aerosol particles) on five A-class event days ranged from 23 to 85%.